Protective Effects of Electroacupuncture at Lr3 on Cardiac Hypertrophy and Apoptosis in Hypertensive Rats. Issue 3 (June 2016) - Chang Lee, Shu-Nu; Ho, Tsung-Jung; Shibu, Marthandam Asokan; Day, Cecilia Hsuan; Viswanadha, Vijaya Padma; Lai, Chao-Hung; Chen, Yi-Li; Hsieh, Dennis Jine-Yuan; Chen, Yueh-Sheng; Huang, Chih-Yang
Objectives: To investigate the effect of electroacupuncture (EA) at LR3 on blood pressure (BP) and cardiovascular remodelling and hypertrophy in male spontaneously hypertensive rats (SHRs). Methods: Healthy Wistar-Kyoto rats were used as normotensive controls (control group, n=9). SHRs either remained untreated (SHR group, n=9) or received EA treatment at LR3 (SHR+LR3 group, n=9) or a nearby non-acupuncture point (SHR+sham group, n=9) for 3 weeks. BP was measured on day 3 and day 19. Samples of left ventricle were stained with haematoxylin and eosin or subjected to terminal deoxynucleotidyl transferase dUTP (deoxyuridine triphosphate) nick end labelling (TUNEL) to assess histology and apoptosis, respectively (n=3 per group). Western blotting was used to determine the relative expression of antioxidants and molecular markers of detoxification capacity, cardiac hypertrophy, and apoptosis (n=5 per group). Results: By day 3, the systolic BP, mean BP, and diastolic BP in the untreated SHRs increased from 169.5±14, 131.6±14, and 112.2±15 mm Hg (at baseline) to 179.6±1, 137.6±4, and 118.7±5 mm Hg, respectively (p<0.001 vs control group). BP in the SHR+LR3 rats was approximately 15 mm Hg lower than the SHR and SHR+sham groups (p<0.05). SHRs also exhibited cardiac hypertrophy (evident from histological and Western blot analyses). However, SHR+LR3 rats showed significant reductions in markers of cardiac hypertrophy and apoptosis, as well as elevated expression of antioxidant enzymes including superoxide dismutase-1 (SOD1). Conclusions: EA at LR3 reduced BP and had positive effects on markers of cardiac apoptosis and hypertrophy in a rat model of hypertension. Thus, EA is a potentially promising intervention to treat cardiovascular remodelling secondary to hypertension.